Effects of Floral Preservatives on The Extension of Vase Life and Quality of Tuberose: Impact of floral preservatives on quality of tuberose - Ashrafun Nahar; Md Harun Ar Rashid; Most Tamanna Tasmim; Mst Mukti Banu; Mst Fatema Tuz Zahura (Research in Agriculture Livestock and Fisheries, 2025)
An experiment was conducted to study the effects of preservative solutions on the extension of vase life of tuberose in the Postharvest Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from 1 August 2023 to 10 August 2023. The experiment consisted of two types of tuberoses viz. single (C1) and double (C2) and five preservative solutions viz., T0= water (control), T1= lemon juice solution (5%), T2= CaCl2 solution (0.05%), T3= aspirin solution (0.03%), and T4= sugar solution (5%). The two-factor experiment was carried out in a Randomized Complete Block Design with 3 replications. Results revealed substantial differences between tuberose types in respect of various parameters under study. Double tuberose performed higher total solution uptake (149.00 ml) and maximum vase life (11.0 days) and gave a lower number of opened and dried florets, compared to single type. There was significant variation among the treatment effects in respect of a number of opened and dried florets, total solution uptake (ml) and vase life. Considering all the parameters studied, it was concluded that double tuberose along with sugar solution performed better in respect of vase life extension and keeping the quality of tuberose compared to other treatments. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 93-103